The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/1098-2752(2000)20:7<343::aid-micr6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Cold storage of rat skeletal muscle free flaps and pre-ischemic perfusion with modified UW solution

Abstract: We used the rat medial gastrocnemius free flap, based on a pedicle of the femoral artery and vein, in order to test the tolerance of skeletal muscle to cold ischemia‐reperfusion (IR) injury, and to determine whether tolerance can be enhanced by pre‐ischemic perfusion with tissue/organ preservation solutions. Muscle flaps (n = 6 per group) were subjected to variable periods of cold storage (0, 1, 2, 3, or 4 days) and 24‐h normothermic reperfusion. Muscle viability, as determined by nitroblue tetrazolium (NBT) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…However, cold-stored skeletal muscle, too, is susceptible to cold ischemia-reperfusion injury, and its viability can be increased by prior perfusion with a tissue preservation solution such as University of Wisconsin solution. 43 Evidence from animal experiments suggests that intraarterial flushing with cold solutions produces a more uniform reduction in temperature for amputated limbs. 44 This is in accord with the current practice of using a modified University of Wisconsin solution for organ flushing before transplantation.…”
Section: Hypothermia and Intraarterial Flushingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cold-stored skeletal muscle, too, is susceptible to cold ischemia-reperfusion injury, and its viability can be increased by prior perfusion with a tissue preservation solution such as University of Wisconsin solution. 43 Evidence from animal experiments suggests that intraarterial flushing with cold solutions produces a more uniform reduction in temperature for amputated limbs. 44 This is in accord with the current practice of using a modified University of Wisconsin solution for organ flushing before transplantation.…”
Section: Hypothermia and Intraarterial Flushingmentioning
confidence: 99%
“…However, if the reanastomosis is planned to be made beyond the ischemic time for flap storage and transport (especially muscle flap), pretreatment with local hypothermia and intraarterial flushing with tissue preservation solution is able to improve the flap viability significantly. 43 Intraarterial flushing has shown significant benefit in the treatment of failing flaps. Physiologic solutions have been modified by adding a free radical scavenger (superoxide dismutase), 47 a combination of a free-radical scavenger and a thrombolytic agent (urokinase and superoxide dismutase, 48 streptokinase), 49 and an anti- …”
Section: Hypothermia and Intraarterial Flushingmentioning
confidence: 99%
“…University of Wisconsin (UW) solution has been widely used in the setting of liver, pancreas, and kidney transplantation. However, it is arguable whether or not UW solution is beneficial for preserving skeletal muscle [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the value for the preservation of allografts is still controversial. Several investigations showed no beneficial or even a deleterious effect of PSP on the survival rate of transplanted free flaps or amputated limbs [11][12][13], whereas other studies [7,14,15] reported increased survival rates after PSP. Unfortunately, it cannot be excluded that these results have been influenced by non-physiological perfusion methods, causing mechanical damage or vasoconstriction [12], or by the non-physiological composition of the perfusate itself, causing cytotoxic damage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it cannot be excluded that these results have been influenced by non-physiological perfusion methods, causing mechanical damage or vasoconstriction [12], or by the non-physiological composition of the perfusate itself, causing cytotoxic damage [7]. Furthermore, in these transplantation studies [7,[11][12][13][14][15], it was impossible to distinguish between effects of PSP on the preservation of the muscle tissue and on the vasculature. These studies focused primarily on the effect of PSP on the morphology, metabolism and survival of muscle tissue.…”
Section: Introductionmentioning
confidence: 99%